A new perspective for mixed-methods evaluations. (September 2015) - Elahi, Sha'ban; Kalantari, Nadia; Hassanzadeh, Mohammad; Azar, Adel
Evaluation is a broad and multifaceted area of study for researchers that requires the use of a combination of research methods—subsequently providing a challenging agenda for policy-makers. The multifaceted nature of the field indicates an urgent need for a comprehensive framework that includes guidelines for researchers and practitioners. There are several important factors in the selection of method(s) for evaluations including an evaluation's paradigm, approach and purpose; this article aims to address each of these and propose a new perspective for evaluations using a mixed-methods approach. Specifically, the article aims to inform a framework to help evaluators select appropriate methods, with special emphasis on the structural components of the working methodologies. Given the significance of the theoretical background of evaluation, a literature review was carried out with the purpose of informing the development of a new perspective for mixed-methods evaluations using a meta-synthesis approach. All related literature including books and papers published in peer-reviewed journals was extracted, studied and analysed via open coding. Thus, the new perspective presented in this article is based on rich and reliable literature and is helpful for evaluators who are interested in using a mixed-methods approach.